PENINGKATAN KEMAMPUAN BELAJAR AL-QUR’AN SISWA MELALUI METODE WAFA - Musolli Musolli (JUMPA : Jurnal Manajemen Pendidikan, 2021)
The Wafa method is a comprehensive, easy and fun learning Al-Qur'an in learning the Qur'an. The learning context aims to simplify and at the same time accelerate the students 'learning method of the Qur'an. The focus of this research is how to implement the Wafa method in improving the students' ability to memorize Al-Qur'an at MI Fathania Sumberanyar Paiton Probolinggo This study used a qualitative approach with a multicasus study design. documentation. Data analysis techniques include data  reduction, data  presentation, drawing conclusions, checking the validity of the findings carried out by extension of participation: tringulation  techniques  and  observation  persistence.  Research information is the principal, wafa coordinator, teachers and students. The  results showed that  The  implementation of  the  wafa method in improving the ability to memorize the Al-Qur'an at MI Fathania, this student starts with memorizing juz 30 of Surah An-Naba backwards, if you  have  memorized  juz  30,  then  proceed  with  memorizing  juz  29 starting from the letter Al-Mulk backwards . At the end of the activity the